(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
Customer satisfaction in service companies must consider several factors, such as punctuality and service quality. The purpose of this study was to determine the effect of punctuality and service quality on customer satisfaction. This research was conducted at the JNE Express Main Branch in Denpasar. The population was all customers who had made at least one delivery. A total of 110 respondents were selected using a purposive sampling method. The analysis showed that punctuality had a positive and significant effect on customer satisfaction, service quality had a positive and significant effect on customer satisfaction, and both punctuality and service quality simultaneously had a positive and significant effect on customer satisfaction. The researchers recommend that JNE Express Main Branch in Denpasar optimize delivery routes, provide realistic delivery times to customers, and better organize items according to destination to facilitate the delivery process.